A pluralist view of nursing ethics - McCarthy, Joan (Nursing philosophy, 2006)
This paper makes the case for a pluralist, contextualist view of nursing ethics. In defending this view, I briefly outline two current perspectives of nursing ethics - the Traditional View and the Theory View. I argue that the Traditional View, which casts nursing ethics as a subcategory of healthcare ethics, is problematic because it (1) fails to sufficiently acknowledge the unique nature of nursing practice; and (2) applies standard ethical frameworks such as principlism to moral problems which tend to alienate or undermine nursing ethical concerns. Alternatively, the Theory View, which aims to build an independent and comprehensive theory of nursing ethics, is also found wanting because it (1) fails to sufficiently acknowledge the heterogeneous nature of nursing practices; (2) overemphasizes the differences and undervalues the similarities between nurses and other health professionals; and (3) assumes that one ethical framework can be meaningfully applied across diverse moral problems and contexts. My alternative, is to argue that nursing ethics inquiry should take a pluralist and critical stance towards available ethical frameworks and the negotiation of the ethical realm. On this view, the search for moral consensus or a unique ethical framework for nursing is replaced by the task of working strategically with multiple frameworks in order to expand the moral agency of nurses and empower them to positively engage with moral uncertainty as an inevitable feature of living a moral life. I conclude by indicating some of the implications that this has for the teaching of nursing ethics.